Evaluation of the seed germination potential of two species, exotic and native, of Fabaceae as a colonization strategy in a degraded environment (Research, Society and Development, 2021)
The seed germination potential of two species of Fabaceae was evaluated as a degraded environment colonization strategy. Seeds of the exotic species Leucaena leucocephala (leucena) and the native Enterolobium contortisiliquum (tamboril) were treated by physical scarification (cooking at 100ºC, 10 min) and chemical (H2SO4 conc., 15 min), cultivated in soil and vermiculite. For both plant species, the high temperature made the seeds impossible, but acid scarification was efficient. Although low, the germination of the native species, 30% and 40%, was twice the exotic one, 15% and 20%, respectively in soil and vermiculite. The control group showed that the type of substrate did not influence the germination process, and here only seeds of the exotic species germinated in the two substrates. Exotic species are aggressively invasive by the low requirement for germination and consequent efficiency of colonization in degraded areas. Under natural conditions, the overcoming of dormancy and seed germination can occur after acid treatment in the stomach of dispersers, such as birds and terrestrial mammals, and the contact with soil moisture. The germination of the native species E. contortisiliquum, superior to the exotic L. leucocephala, configures a strategic advantage of the native species (long-term pioneer/early secondary) of semideciduous forest and confirms its ecological role for the recovery of degraded areas of the Atlantic Forest domain in the state of Bahia (Brazil).